Performance of Microbial Fuel Cell to Generate Bioelectricity Uses Different Kinds of Electrode in the Fish Processing Wastewater - Bustami Ibrahim; Pipih Suptijah; Zhalindri Noor Adjani (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Microbial Fuel Cell (MFC) is one of the alternative technologies which can convert chemical energy to electrical energy through a catalytic reaction using microorganisms. The technology can be implemented for wastewater handling such as fish processing wastewater which contains highly in organic substances. The research objective was to measure the performance of MFC system using fishery processing wastewater in order to generate bioelectricity and to reduce its organic pollution load within a different material of the electrode. The electrode materials used were aluminum, iron, carbon graphite, and also the combination of aluminum and carbon graphite. The research carried out in three phases: production of fishery wastewater, assembly of MFC single chamber system and measurement of the bioelectricity produced. The bioelectricity power resulted during 120 hours of observation were 0.23V for aluminum, 0.17V for iron, 0.19V for carbon graphite, and 0.34V for the combination between aluminum and carbon graphite averagely. The MFC system can also decrease the organic load parameter of wastewater as much as total Nitrogen was 61%, BOD 30.11%, COD 59.34%, and total Nitrogen Ammonia 12.45%. The increasing of activated sludge biomass occurred on the last observation with MLSS and MLVSS values respectively 7,066.67 mg/L and 6,100 mg/L.